Management of Circuit Air in Extracorporeal Membrane Oxygenation: A Single Center Experience. Issue 3 (March 2022) - Chan, Kai Man; Wan, Winnie Tsz Pan; Ling, Lowell; So, Jack Mei Chun; Wong, Constance Hau Ling; Tam, Sandy Bik Shan
Abstract : Air in circuit in patients receiving extracorporeal membrane oxygenation (ECMO) is an emergency. Different protocols have been suggested to deal with this rare but fatal complication, but their efficacies are rarely reported. We report our institutions' experience in the management of circuit air in Cardiohelp HLS ECMO system. Between October 2009 and July 2020, 4 out of 116 patients developed gas bubbles in ECMO circuit or systemic gas embolism. The clinical characteristics of these patients, source of air, presence of arterial air or pump airlock, cardiorespiratory status during the event, techniques employed to re-establish flow, ECMO downtime, neurologic, and other clinical outcomes were reported. In all cases, the source of air was located, with three of them being on the venous side of the circuit. Centrifugal pump airlock with cessation of ECMO flow was reported in two patients. Strategies used to re-establish ECMO flow included circuit change or deairing using backflush technique. All patients were weaned from ECMO, and three of them were discharged from hospital alive. With effective management, systemic gas embolism could be avoided during air in circuit emergencies. Backflush technique is a safe and effective deairing method to overcome centrifugal pump airlock in Cardiohelp HLS system.